2002
DOI: 10.1182/blood-2002-01-0283
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in the extracellular matrix as a determinant of cardiovascular risk: association of type III collagen COL3A1 polymorphisms with coronary artery disease

Abstract: Although common genetic variants in platelet collagen receptors influence platelet activation and thrombosis, the impact of polymorphisms in collagen genes on cardiovascular disease is unknown. To evaluate this, we genotyped a highly polymorphic intronic tandem repeat of the COL3A1 gene, encoding collagen type III, alpha 1. This revealed 4 common alleles (COL3A1-1, -2, -3, and -4). The 2 populations studied were as follows: (1) a cross-sectional study of 703 acute coronary syndrome (ACS) patients with myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…One example was the Col3a1 gene, which encodes collagen III that is expressed in blood vessels and appears together with collagen I in thickened intima of atherosclerotic lesions and most likely contributes to plaque growth and narrowing of arterial lumen (35). Another notable down-regulated gene was the Svil gene, the encoded protein of which, supervillin, is an F-actin-binding protein implicated in migration, adhesion, and signal transduction to the cell nucleus (36).…”
Section: Table II Genes Regulated By Ha12 In Brain Capillary Endothelmentioning
confidence: 99%
“…One example was the Col3a1 gene, which encodes collagen III that is expressed in blood vessels and appears together with collagen I in thickened intima of atherosclerotic lesions and most likely contributes to plaque growth and narrowing of arterial lumen (35). Another notable down-regulated gene was the Svil gene, the encoded protein of which, supervillin, is an F-actin-binding protein implicated in migration, adhesion, and signal transduction to the cell nucleus (36).…”
Section: Table II Genes Regulated By Ha12 In Brain Capillary Endothelmentioning
confidence: 99%
“…Forty-five of these genes have been implicated previously in CVD (24 genes) [24][25][26] and T2D (21 genes). 14,27,28 Five of the 8 commonly enriched pathways, namely, HCM, dilated cardiomyopathy, ARVC, focal adhesion, and extracellular matrix-receptor interaction signaling, were also found to be highly interconnected as demonstrated by a shared common set of 117 genes among them ( Figure 1). Besides the shared pathways across diseases and ethnicities, we also identified disease-and ethnicity-specific pathways (Table VIII in the Data Supplement).…”
Section: Identification Of Biological Pathways Using Integrative Pathmentioning
confidence: 99%
“…This includes genetic studies (6)(7)(8)(9)(10). In spite of this extensive research, a practical and reliable index of platelet activation has not been found.…”
mentioning
confidence: 98%